(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The importance of information technology in the topic of vectors in analytic geometry is emphasized in the article. Features such as the student’s mood, interests, lifestyle, worldview, thinking, mental, and professional talents come into play when planning education on the basis of new technologies. Engaging students as active participants in the class and encouraging them to act produces excellent results today. In today’s fastpaced world, there is debate of expanding young people’s access to computer educational technology, attracting them to work more on themselves, and increasing the use of ICTs in educational processes